ANALISIS PENGARUH INFLASI, TINGKAT SUKU BUNGA SBI DAN NILAI TUKAR TERHADAP JUMLAH UANG YANG BEREDAR DI INDONESIA Periode 2001 s/d 2006 - Yuliana, SE., MM,, Indah (Fakultas Ekonomi, UIN Maliki Malang, 2008)
There are many macro economic indicators which is usually used to measure wheel growth of state, for example that is inflation, exchange rate, rate of interest storey; level and also the amount of money supplies in state. Distortion movement of difficult exchange rate in order to be known and forecasted. it exchange rate very base on various factor, among others that is moneys amount and inflation circulating. Moneys amount circulating by relative influence exchange rate. Whether in home affairs and in international world. A currency will decrease the value of if moneys amount circulating more. Each there is sign indicating that the amount of moneys circulating to grow swiftly hence surely the money available in number many and the him of declining. Strength of economics fundamental a state in emulation in world market reflected to through dealt only with state currency value is other state. If real sector can print surplus to trade partner state, relatively will strengthen and improve currency value and if real sector asset productivity not optimal hence balance of trade and transaction will experience of deficit. This influence exchange rate depressions, so that have no other way to except isn't it currency on the chance of domestic product competitiveness can mount sold cheaper product to global market. This Research target is first is to see influence of inflation, rate of interest storey; level of SBI and exchange rate by simulate to moneys amount circulating in Indonesia, secondly is among inflation, rate of interest storey; level of SBI and exchange rate, which was which is dominant of influence of to moneys amount circulating in Indonesian. Analyzer the used is doubled linear regress. This Research result is ( 1) By simulate inflation, level of SBI and exchange rate have an effect on to moneys amount circulating in Indonesia period 2001 to 2006. (2) Variable mount rate of interest of SBI is dominant Variable of influence of to moneys amount circulating in Indonesia period 2001 to 2006.